Monitoring of drug interactions in elderly patients with benign prostatic hyperplasia and cardiovascular diseases - Lazarević, Katarina; Marković, Aleksandra; Vezmar Kovačević, Sandra; Jovanović, Marija; Ćulafić, Milica; Kovačević, Milena; Vučićević, Katarina; Miljković, Branislava (Archives of Pharmacy, 2022)
Benign prostatic hyperplasia (BPH) represents a non-cancerous prostate enlargement associated with lower urinary tract symptoms and is one of the most common diseases in older men. As comorbidities, primarily cardiovascular diseases (CVD) are common in this age group, a great number of clinically significant drug interactions can be expected. The aim of this research was to estimate the frequency and type of potential interactions in the treatment of elderly with BPH and CVD. A retrospective study included 93 men aged over 65 with BPH and hypertension or CVD. Patients’ data were collected from medical records. Potential interactions were identified and assessed using the Lexicomp® database. Descriptive analysis was performed in Microsoft® Office Excel 2010. Patients’ average age was 75.3±6.05. The number of drugs in therapy ranged from 2 to 13. Five or more drugs were used by 72.04% of the patients. A total of 509 interactions were detected, of which 467 are clinically significant (C, D, X). Most interactions belonged to category C (85.46%), while 4.91% belonged to class D, and only 1.38% to class X. Within class X, which indicates that concomitant use of drugs should be avoided, the interaction between the two α-blockers was most frequent. 412 pharmacodynamic and 47 pharmacokinetic interactions were identified. The dual mechanism was detected in 29 interactions, while for 21 the mechanism was unknown. The obtained results suggest the involvement of pharmacists in the monitoring of patients with BPH may be useful, given the great proportion of identified clinically significant interactions.